Analysis of the Segregation Distortion of FcRAN1 Genotypes Based on Whole-Genome Resequencing of Fig (Ficus carica L.) Breeding Parents - Ikegami, Hidetoshi; Shirasawa, Kenta; Yakushiji, Hiroshi; Yabe, Shiori; Sato, Masaru; Hayashi, Takeshi; Tashiro, Kosuke; Nogata, Hitoshi (Frontiers in Plant Science, 2021)
The common fig (Ficus carica L.) has a gynodioecious breeding system, and its sex phenotype is an important trait for breeding because only female plant fruits are edible. During breeding to select for female plants, we analyzed the FcRAN1 genotype, which is strongly associated with the sex phenotype. In 12 F1 populations derived from 13 cross combinations, the FcRAN1 genotype segregation ratio was 1:1, whereas the M119-226 × H238-107 hybridization resulted in an extremely male-biased segregation ratio (178:7 = male: female). This finding suggests that the segregation distortion was caused by some genetic factor(s). A whole-genome resequencing of breeding parents (paternal and maternal lines) identified 9,061 high impact SNPs among parents. A genome wide linkage analysis (GWLA) exploring responsible gene(s) for the distortion revealed 194 high-impact SNPs were specific to Caprifig6085 as seed parent ancestor and 215 high-impact SNPs were specific to H238-107 as pollen parent in 201 annotated genes. Collating the annotated genes with the genes required for normal embryo or gametophyte development and function suggested that at least several genes become candidates responsible for the segregation distortion. This is the first report describing segregation distortion in F. carica.